The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1021/jf980223x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Catechins, Gallic Acid, and Methylxanthines in Green, Oolong, Pu-erh, and Black Teas

Abstract: An isocratic HPLC procedure was developed for simultaneous determination of six catechins, gallic acid, and three methylxanthines in tea water extract. A baseline separation was achieved on a Cosmosil C18-MS packed column with a solvent mixture of methanol/doubly distilled water/formic acid (19.5:80.2:0.3, v/v/v) as mobile phase. A gradient HPLC procedure was also provided for the separation of these tea components. The contents of catechins, gallic acid, and methylxanthines have been measured in infusions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
177
0
7

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(206 citation statements)
references
References 20 publications
18
177
0
7
Order By: Relevance
“…Dietary antioxidants are found in cereals, fruits, legumes, spices, vegetables and beverages (Ganthavorn & Hughes, 1997;Lin et al, 1998;Kalt et al, 1999;Ewald et al, 1999;Che Man & Tan, 1999;Markus et al, 1999). The contribution of total PPs to antioxidant capacity has been extensively studied in fruits and vegetables (Furuta et al, 1997;Gazzani et al, 1998;Heinonen et al, 1998;Saleh et al, 1998;Wang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary antioxidants are found in cereals, fruits, legumes, spices, vegetables and beverages (Ganthavorn & Hughes, 1997;Lin et al, 1998;Kalt et al, 1999;Ewald et al, 1999;Che Man & Tan, 1999;Markus et al, 1999). The contribution of total PPs to antioxidant capacity has been extensively studied in fruits and vegetables (Furuta et al, 1997;Gazzani et al, 1998;Heinonen et al, 1998;Saleh et al, 1998;Wang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that gallic acid was the main radical scavenger in Toyama Kurocha. It has been reported that gallic acid is a main catechin of the late-fermented teas Kurocha and Pu-erh tea, and could be separated from (-)-epicatechin gallate while other catechins were polymerized during fermentation of the tea (Shojaku et al, 1984;Lin et al, 1998;Matsumoto et al, 1999). However, the radical scavenging activity of gallic acid in the late-fermented tea was not studied in these papers.…”
Section: Resultsmentioning
confidence: 99%
“…GOTO et al [11] acharam níveis comparáveis de EGC e EC, mas maiores de EGCG e ECG, enquanto DING et al [7] relataram níveis mais altos de EC, que foi a principal catequina, e ECG. LIN et al [19] apresentaram níveis nitidamente mais altos de ECG e menores de EGC. Por sua vez, SHAO et al [26] acharam ECG como principal catequina, além de conteúdos mais altos de EC.…”
Section: -Teores De Catequinasunclassified